Impact of fluvoxamine on outpatient treatment of COVID-19 in Honduras in a prospective observational real-world study - Pineda, Estela; Singh, Jarmanjeet; Pineda, Miguel Vargas; Umanzor, Jose Garay; Baires, Fernando; Benitez, Luis G.; Burgos, Cesar; Sekhon, Anupamjeet Kaur; Crisp, Nicole; Lewis, Anita S.; Radwanski, Jana; Bermudez, Marco; et al. (Frontiers in Pharmacology, 2022)
Background: The COVID-19 pandemic has impacted millions of lives globally. While COVID-19 did not discriminate against developed or developing nations, it has been a significant challenge for third world countries like Honduras to have widespread availability of advanced therapies. The concept of early treatment was almost unheard of when early outpatient treatments utilizing repurposed drugs in Latin American countries began showing promising results. One such drug is fluvoxamine, which has shown tremendous potential in two major studies. As a direct result, fluvoxamine was added to the standard of care in a major medical center outpatient COVID-19 clinic. Methods: This prospective observational study was performed at the COVID-19 outpatient clinic of the Hospital Centro Médico Sampedrano (CEMESA) in San Pedro Sula, Cortes, Honduras. All patients who were fifteen years or older, who had presented with mild or moderate signs and symptoms of COVID-19, and had a documented positive SARS-CoV-2 antigen or Reverse Transcription Polymerase Chain Reaction (RT-PCR) were included in the study. Fluvoxamine was prescribed to all patients. The cohort of patients who decided to take fluvoxamine were compared for primary endpoints of mortality and hospitalization risk to the cohort who did not take fluvoxamine. Categorical variables were compared by Pearson Chi-square test. The Relative risk was calculated using regression models. Continuous variables were compared by t-test and Wilcoxon rank-sum tests. Results: Of 657 total COVID-19 cases, 594 patients took fluvoxamine and 63 did not. A total of five patients (0.76 percent) died, with only one death occurring in the fluvoxamine group. Patients who received fluvoxamine had a significantly lower relative risk of mortality (RR 0.06, p 0.011, 95%CI 0.007 to 0.516). There was a lower relative risk of hospitalization in the fluvoxamine group. (- 10 vs 30 hospitalizations, RR 0.49, p=0.035, 95%CI 0.26-0.95). There was 73 percent reduction in relative risk of requiring oxygen in the fluvoxamine group (RR 0.27, p<0.001, 95%CI 0.14-0.54) Conclusion: The results of our study suggest that fluvoxamine lowers the relative risk of death, hospitalization, and oxygen requirement in COVID-19 patients.